Keyboard circuit trace restoration using conductive silver paste for computer input devices - Moh Muchlishiin; Aprima A Matondang; Cholish Cholish; Thea Fitri Astarani; Haksa Sinambela (Institute of Computer Science (IOCS), 2026)
Computer keyboards serve as essential input devices that translate user actions into digital signals. One common failure mechanism in keyboard membranes involves broken or degraded circuit traces, which leads to non-functional keys. This study investigates the restoration of such traces using conductive silver paste. An experimental approach was adopted, involving the repair of damaged traces on flexible membrane keyboard PCBs, followed by electrical testing and durability observation. The measurement outcomes indicate that silver paste offers approximately 7% higher electrical conductivity relative to copper, with measured resistivity at 15.87 nΩ·m and thermal conductivity reaching 430 W/m·K. Open circuit conditions (infinite resistance) were successfully restored to functional conductive paths showing 3.5 ± 0.8 Ω resistance after paste application and controlled heat curing. The post-repair resistance represents only a 25% increase compared to the original intact trace value of 2.8 ± 0.5 Ω, which remains well within the acceptable range for digital keyboard applications. This research contributes practical guidance for computer hardware maintenance personnel and researchers focused on input device reliability, while also supporting sustainable practices through repair-based lifecycle extension